Ultra-endurance exercise: unanswered questions in redox biology and immunology. (11th August 2014) - Turner, James E.; Bennett, Stuart J.; Bosch, Jos A.; Griffiths, Helen R.; Aldred, Sarah
Abstract : Ultra-endurance races are extreme exercise events that can take place over large parts of a day, several consecutive days or over weeks and months interspersed by periods of rest and recovery. Since the first ultra-endurance races in the late 1970s, around 1000 races are now held worldwide each year, and more than 100000 people take part. Although these athletes appear to be fit and healthy, there have been occasional reports of severe complications following ultra-endurance exercise. Thus there is concern that repeated extreme exercise events could have deleterious effects on health, which might be brought about by the high levels of ROS (reactive oxygen species) produced during exercise. Studies that have examined biomarkers of oxidative damage following ultra-endurance exercise have found measurements to be elevated for several days, which has usually been interpreted to reflect increased ROS production. Levels of the antioxidant molecule GSH (reduced glutathione) are depleted for 1 month or longer following ultra-endurance exercise, suggesting an impaired capacity to cope with ROS. The present paper summarizes studies that have examined the oxidative footprint of ultra-endurance exercise in light of current thinking in redox biology and the possible health implications of such extreme exercise.